An aryl-bridged dixanthene scaffold for building multinucleating ligands and supramolecular assemblies: Syntheses and structures. Issue 45 (9th November 2017) - Mudge, Matthew; Patel, Alpesh Ramanlal; Bingül, Murat; Bhadbhade, Mohan; Colbran, Stephen B.
Abstract: An aryl-bridged dixanthene scaffold is quickly prepared and readily derivatized with functional groups at the four 4, 5-positions adjacent to the oxygen atoms of the two xanthene groups: syntheses of five potentially tetradentate, multinucleating, metal-binding ligands illustrate the usefulness of the methodology. Graphical abstract: